Соціальні медіа – на межі між особистим і професійним розвитком - Tepavicharova, Milena; Dikova, Lyudmila (Dr. Viktor Koval, 2019)
Introduction. Social media steadily and constantly envelops all aspects of peoples' lives. Thus it is of crucial importance to investigate and measure social media activities' impact on their inclusion in the formation of today’s and future societies as more and more online activities have been incorporated in real life personal and professional activities. Aim and tasks. This article explores the new trends in people’s activities at the workplace and outlines the main concerns regarding keeping the line between personal and professional online activities. Results. Social media are now an integral part of the everyday life of modern man. Since a person spends most of their day at work or in pursuit of their profession, they also seek to engage in personal activities within the working day (talking on the phone with family or friends, shopping online, reading news etc.). A user is created with features specific to the internet generation. This new type of user has specific features that allow researchers to talk about the emergence of a next-generation user. The Next Generation User is a person who has access to the Internet from multiple locations and devices.The rapid penetration of social media in people's everyday life implies a greater impact on all users' real-life and online activities. Evidence of the latter can be found in very common situations when users upload photos or videos from parties or events in real time not always tacking into consideration the possible outcomes for their personal and professional lives. Conclusions. Managers consider that workers should focus more not only on the technical limitation of the exchange in of information on social media but also on a better personal judgment about the nature and volume of the shared information. The intensity of social media activities of the workers is monitored actively by employers and coworkers alike and can be seen as an indicator of low efficiency or irresponsible personality. With the fast development of wireless mobile telecommunications technology and the growing multitude of mobile apps online activities become a real threat for workers’ productivity and the development of workplace culture.